Answer
One Solution: (-1, -2)
![](https://gradesaver.s3.amazonaws.com/uploads/solution/69585465-4d2e-4b6a-9940-d8ed31fcf963/result_image/1513220504.png?X-Amz-Algorithm=AWS4-HMAC-SHA256&X-Amz-Credential=AKIAJVAXHCSURVZEX5QQ%2F20250118%2Fus-east-1%2Fs3%2Faws4_request&X-Amz-Date=20250118T040516Z&X-Amz-Expires=900&X-Amz-SignedHeaders=host&X-Amz-Signature=c5a51660ac2d033a038df1c5e6679bc315abcbd0e647c8895364f89f6464ccac)
Work Step by Step
Our two equation are:
1. y=x-1
2. y=-3x-5
We can use substitution and set the two equations above equal to each other because both equations equal to y.
x-1=-3x-5 (Add 3x to both sides)
4x-1=-5. (Add 1 to both sides)
4x=-4 (Divide by -4 from both sides)
x=-1
Now that we know the value of x, lets plug it into our first equation to find the value of y.
y=-1-1
y=-2
So our solution is (-1, -2)